2010
DOI: 10.3390/toxins2122872
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Treating Motor Neuron Diseases Using a Fusion Protein of Botulinum Toxin Binding Domain and Streptavidin for Viral Vector Access: Work in Progress

Abstract: Although advances in understanding of the pathogenesis of amyotrophic lateral sclerosis (ALS) and spinal muscular atrophy (SMA) have suggested attractive treatment strategies, delivery of agents to motor neurons embedded within the spinal cord is problematic. We have designed a strategy based on the specificity of botulinum toxin, to direct entry of viral vectors carrying candidate therapeutic genes into motor neurons. We have engineered and expressed fusion proteins consisting of the binding domain of botulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Alternatively this might be explained by differences in affinity of BoNT subtypes, as it was reported that BoNT/B2 may be more active than BoNT/B1 29 . This finding could be of specific importance since HcB has potential for the development of protective recombinant vaccines against botulism, and to target specific drugs to nerve terminals 35 , 36 .…”
Section: Discussionmentioning
confidence: 97%
“…Alternatively this might be explained by differences in affinity of BoNT subtypes, as it was reported that BoNT/B2 may be more active than BoNT/B1 29 . This finding could be of specific importance since HcB has potential for the development of protective recombinant vaccines against botulism, and to target specific drugs to nerve terminals 35 , 36 .…”
Section: Discussionmentioning
confidence: 97%